Bismuth oxyhalide carbon composite material as well as preparation method and application thereof
By loading MOFs in woody carbon materials and performing high-temperature carbonization, combined with the surface modification of bismuth oxyhalide, we designed an efficient bismuth oxyhalide carbon composite material, which solved the resource consumption and environmental pollution problems of traditional seawater desalination technology and achieved Efficient photothermal water evaporation and photocatalytic degradation.
Patent Information
- Application Number
- CN202411413286.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-21
AI Technical Summary
Traditional energy-driven seawater desalination technology has the problem of excessive consumption of fossil energy and environmental pollution, and the utilization rate of natural wood carbon materials is low and the biological value is not fully utilized.
By loading porous MOFs materials in wood carbon materials and performing high-temperature carbonization, combined with surface modification of bismuth oxyhalide, a bismuth oxyhalide carbon composite material is designed to achieve efficient photothermal conversion and photocatalytic degradation.
This material significantly improves the evaporation efficiency of light and hot water and the performance of photocatalytic degradation. Compared with natural wood carbon materials and bismuth oxyhalide carbon composite materials without MOFs, the evaporation efficiency is increased to 85.27%, and the degradation rate is also significantly improved.
Smart Images

Figure CN119327488A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photothermal water treatment, and specifically relates to a bismuth oxyhalide carbon composite material and a preparation method and application thereof. Background Art
[0002] Clean water resources are closely related to many aspects of human survival activities, such as energy and food production, health, industry, and ecological balance. However, with the rapid population growth and vigorous industrial development in recent decades, water pollution has become increasingly serious. In order to alleviate the water shortage crisis in the development of human society, seawater desalination technology is gradually becoming one of the main water treatment methods. However, traditional energy-driven seawater desalination technology has problems such as excessive consumption of fossil energy such as coal and aggravated environmental pollution. Solar-driven seawater desalination technology can use inexhaustible solar energy resources to drive the evaporation of water in salt water (seawater, brackish water, etc.) through the photothermal effect, and finally obtain clean water resources. This technology consumes less resources and has less environmental pollution, providing a new way to solve the problem of water shortage.
[0003] A typical solar evaporator contains two key components: photothermal conversion materials and water transport materials. An ideal solar evaporator should have the characteristics of strong light absorption, low heat loss, rapid water transport and low evaporation enthalpy. Among the many photothermal materials, wood carbon materials have attracted much attention from researchers due to their advantages such as abundance, low cost, good hydrophilicity and rich pore structure. Wood carbon can provide continuous and stable water transport for the thermal interface. At the same time, the micron-scale channels of wood carbon itself contain abundant hydrophilic oxygen-containing functional groups, which provide a natural framework for changing the hydrogen bonding state of water and regulating its evaporation enthalpy. However, the utilization rate of natural wood carbon materials is low, and their biological value has not been fully utilized. Therefore, other functional materials can be loaded into the wood channels, and the wood carbon materials can be modified and converted into an efficient photocatalytic-photothermal integrated system, which not only provides new ideas for solar-driven seawater desalination, but also creates possibilities for the efficient treatment of oily wastewater.
[0004] Metal organic frameworks (MOFs) have broad application prospects in the fields of catalysis, adsorption and separation. By loading MOFs in wood carbon materials, it is beneficial to stabilize the pore structure and improve the performance of photothermal water evaporation. Among many semiconductor photocatalysts, bismuth oxyhalide has a moderate band gap and is non-toxic. The photoexcited electrons in the crystal can easily transfer from the valence band to the conduction band through a certain band gap, thereby achieving high photocatalytic absorption. In order to solve the problem of designing the pores required for absorption and considering the cost of raw materials, our goal is to design a bismuth oxyhalide carbon composite material with efficient photothermal conversion and photocatalytic degradation capabilities by adopting high-temperature carbonization, MOFs-assisted carbonization and bismuth oxyhalide surface modification, coupling photothermal water evaporation and photocatalytic degradation performance, thereby achieving efficient collection of clean water. Summary of the invention
[0005] In order to comprehensively solve the above problems, the purpose of the present invention is to provide a bismuth oxyhalide carbon composite material and its preparation method and application, so as to integrate the performance of photothermal water evaporation and photocatalytic degradation to achieve efficient collection of clean water.
[0006] In order to achieve the above object, the first aspect of the present invention provides a bismuth oxyhalide carbon composite material, comprising wood carbon and bismuth oxyhalide composited on the wood carbon. The bismuth oxyhalide is any one of bismuth oxychloride, bismuth oxybromide or bismuth oxyiodine; the mass ratio of bismuth oxyhalide to carbon is 1:(50-200).
[0007] A second aspect of the present invention provides a method for preparing a bismuth oxyhalide carbon composite material, comprising:
[0008] Step 1: Mixing a transition metal salt and a solvent to prepare a solution A, placing wood in the solution A to load the transition metal on the wood by a hydrothermal method, and then performing solid-liquid separation to obtain a wood precursor loaded with the transition metal;
[0009] Step 2: Mixing an organic ligand and a solvent to prepare a solution B, placing wood in the solution B, loading MOFs on the wood precursor by a hydrothermal method, and then performing solid-liquid separation and freeze drying to obtain a wood precursor loaded with MOFs;
[0010] Step 3: Carbonizing the wood precursor loaded with MOFs in step 2 at high temperature under an inert atmosphere to obtain a MOFs-loaded wood-derived carbon material;
[0011] Step 4: Mix the bismuth salt, the halide salt and the solvent to form a solution C, prepare bismuth oxyhalide on the MOFs-loaded derived wood carbon material by a hydrothermal method, and then separate the solid and liquid to obtain a bismuth oxyhalide carbon composite material.
[0012] Preferably, in step 1:
[0013] The transition metal salt is any one of nickel salt, iron salt, zinc salt or cobalt salt;
[0014] The solvent is any one or more of methanol, anhydrous ethanol or deionized water.
[0015] Preferably, in step 2:
[0016] The organic ligand is any one of 2-methylimidazole, 4-methylimidazole, 4,5-methylimidazole and 4,4'-methylimidazole;
[0017] The solvent is one or more of methanol, anhydrous ethanol and deionized water;
[0018] The mass ratio of MOFs to wood precursor is 1:(10-100).
[0019] Preferably, in step 1 and step 2:
[0020] The concentrations of the transition metal salt in step 1 and the organic ligand in step 2 are both 0.1-1.0 mol / L;
[0021] The hydrothermal temperature is 50-100°C and the time is 10-20h;
[0022] The freeze-drying temperature is -20 to -50°C and the time is 24 to 48 hours.
[0023] Preferably, in step 3:
[0024] The carbonization temperature is 600-900°C and the carbonization time is 1-3h;
[0025] The carbonization heating rate is 3-10°C / min; the flow rate of the inert gas flow is 50-200mL / min.
[0026] Preferably, in step 4:
[0027] The concentrations of bismuth salt and bromide salt are both 0.1-1.0 mol / L;
[0028] The hydrothermal temperature is 100-200°C, and the hydrothermal time is 3-10 hours.
[0029] Preferably, in step 4:
[0030] The bismuth salt is any one of bismuth nitrate, bismuth chloride and bismuth sulfate;
[0031] The halide salt is any one of potassium halide and sodium halide;
[0032] The solvent is one or more of glacial acetic acid, anhydrous ethanol and deionized water.
[0033] A third aspect of the present invention provides a bismuth oxyhalide carbon composite material for use in coupling solar water evaporation and photocatalytic degradation of oily wastewater.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The present invention provides a method for preparing a bismuth oxyhalide carbon composite material, which uses abundant and inexpensive wood as a carbon source to prepare a wood carbon material, greatly reducing the preparation cost and providing a new idea for the high-value utilization of wood. In addition, the preparation method has a simple preparation process, convenient operation, is suitable for industrial-scale production, and has a good industrial application prospect;
[0036] 2. The bismuth oxyhalide carbon composite material prepared by the present invention introduces a large number of pore structures into natural wood by loading porous MOFs materials and performing high-temperature carbonization. This composite material has the advantages of rich pores and large specific surface area, and can provide continuous and stable water transport for the thermal interface. Its evaporation efficiency is significantly improved to 85.27% compared with natural wood and bismuth oxyhalide carbon composite materials not doped with MOFs;
[0037] 3. The bismuth oxyhalide carbon composite material prepared by the present invention can promote the full oxidation of organic pollutants on the surface of bismuth oxyhalide nanosheets by utilizing the excellent adsorption performance of wood carbon materials. This material exhibits efficient photocatalytic activity under visible light and has an excellent degradation effect on organic pollutants in water bodies. Compared with the single bismuth oxyhalide nanosheets, its degradation rate is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.
[0039] In the attached picture:
[0040] Figure 1 The photos of the raw materials at different processing stages in Example 1 of the present invention, wherein (a) is natural wood, (b) is a wood precursor loaded with ZIF-67, (c) is a carbonized ZIF-67@wood carbon material, and (d) is a bismuth oxyhalide carbon composite material;
[0041] Figure 2 This is a scanning electron microscope image of the bismuth oxyhalide carbon composite material in Example 1 of the present invention;
[0042] Figure 3 The X-ray diffraction patterns of the bismuth oxyhalide carbon composite materials in Example 1 and Comparative Examples 1 to 3 of the present invention;
[0043] Figure 4 The mass change curves of Examples 1 to 4 of the present invention and a blank experiment under sunlight;
[0044] Figure 5 The degradation rate curves of rhodamine b (RhB) in Example 1 of the present invention, Comparative Example 1 and BiOBr under sunlight;
[0045] Figure 6 This is the cyclic stability curve of RhB degradation under sunlight in Example 1 of the present invention;
[0046] Figure 7 The present invention is a flow chart of the preparation method of the bismuth oxyhalide carbon composite material. DETAILED DESCRIPTION
[0047] In order to enable those skilled in the art to better understand the technical solution of the present invention and to implement it, the following is a detailed description of the technical solution of the present invention in combination with the specific embodiments and the attached drawings. Figure 1 -Attached Figure 7 The present invention is further described below, but the embodiments are not intended to limit the present invention.
[0048] A first aspect of the present invention provides a bismuth oxyhalide carbon composite material, comprising wood carbon and bismuth oxyhalide composited on the wood carbon.
[0049] The bismuth oxyhalide is any one of bismuth oxychloride, bismuth oxybromide or bismuth oxyiodine;
[0050] The mass ratio of bismuth oxyhalide to wood carbon is 1:(50-200)).
[0051] like Figure 7 The second aspect of the present invention provides a method for preparing a bismuth oxyhalide carbon composite material, comprising:
[0052] Step 1: Mix a transition metal salt (concentration 0.1-1.0 mol / L) and a solvent to prepare a solution A, load the transition metal on the wood by a hydrothermal method (temperature 50-100°C, time 10-20h), and then separate the solid and liquid to obtain a wood precursor loaded with the transition metal.
[0053] The transition metal salt is any one of nickel salt, iron salt, zinc salt or cobalt salt;
[0054] The solvent is any one or more of methanol, anhydrous ethanol or deionized water.
[0055] Step 2: Mix the organic ligand (concentration of 0.1-1.0 mol / L) and the solvent to prepare solution B, load MOFs on the wood precursor in step 1 by a hydrothermal method (temperature of 50-100°C, time of 10-20h), then separate the solid and liquid and freeze-dry, wash and freeze-dry at -20 to -50°C for 24 to 48h to obtain the wood precursor loaded with MOFs.
[0056] The organic ligand is any one of 2-methylimidazole, 4-methylimidazole, 4,5-methylimidazole and 4,4'-methylimidazole;
[0057] The solvent is one or more of methanol, anhydrous ethanol and deionized water;
[0058] The mass ratio of MOFs to wood precursor is 1:(10-100).
[0059] Step 3: The wood precursor loaded with MOFs in step 2 is carbonized at a high temperature of 600-900°C for 1-3h under an inert atmosphere, and the flow rate of the inert gas flow is 50-200mL / min, and finally a derivative wood carbon material loaded with MOFs is obtained; wherein the heating rate of high temperature carbonization is 3-10°C / min.
[0060] The inert gas includes any one of nitrogen and argon.
[0061] Step 4: Mix bismuth salt, halide salt and solvent to form solution C, prepare bismuth oxyhalide on the MOFs-loaded wood-derived carbon material by hydrothermal method, and then separate the solid and liquid to obtain bismuth oxyhalide carbon composite material. The concentration of bismuth salt and bromine salt is 0.1-1.0 mol / L, the temperature of hydrothermal reaction is 100-200°C, and the time is 3-10 hours.
[0062] The bismuth salt includes any one of bismuth nitrate, bismuth chloride and bismuth sulfate;
[0063] The halide salt includes any one of potassium halide and sodium halide;
[0064] The solvent includes one or more of glacial acetic acid, anhydrous ethanol and deionized water.
[0065] A third aspect of the present invention provides a bismuth oxyhalide carbon composite material for use in coupling solar water evaporation and photocatalytic degradation of oily wastewater.
[0066] Example 1
[0067] Sources of materials involved in this embodiment: The wood used is balsa wood, which was purchased from Shengyuan Wood Industry Co., Ltd. Cobalt nitrate hexahydrate (Co(NO3)2·6H2O, 99%) and 2-methylimidazole (2-MeIm, 98%) were purchased from Shanghai McLean Reagent Co., Ltd., China. Bismuth nitrate pentahydrate (Bi(NO3)3·5H2O, 99%), potassium bromide (KBr, 99%) and rhodamine B (RhB, AR) were purchased from Shanghai Aladdin Reagent Co., Ltd., China. The water used in the experiment was all deionized water. The wood was purchased from "Lind Toys Store" on Taobao "DIY Handmade Sand Table Building Model Balsa Wood Airplane Wooden Airplane Model Material Round Wood Stick Light Square Wood Strip".
[0068] A method for preparing a bismuth oxyhalide carbon composite material, comprising:
[0069] Step 1: Co(NO3)2 (0.5 mol / L) was mixed with ionized water and anhydrous ethanol in a 100 mL polytetrafluoroethylene-lined reactor to prepare 2+ Solution (Solution A), a 1.5 cm cube of wood was placed in 80 mL of Co 2+The solution was subjected to a hydrothermal reaction at a temperature of 80°C. After the reaction, solid-liquid separation was performed to obtain the loaded Co 2+ of wood precursors;
[0070] Among them, the volume ratio of ionized water and anhydrous ethanol is 1:1;
[0071] Step 2: 2-Methylimidazole (0.5 mol / L) was mixed with ionized water and anhydrous ethanol in a 100 mL polytetrafluoroethylene-lined reactor to prepare an organic ligand solution (solution B). 2+ The wood precursor is placed in 80 mL of organic ligand solution, the reaction temperature is controlled to be 80°C, and after the reaction is completed, solid-liquid separation is performed to obtain the wood precursor loaded with ZIF-67;
[0072] The solute of the organic ligand solution is 2-methylimidazole (0.5 mol / L), and the solvent is deionized water and anhydrous ethanol (volume ratio is 1:1).
[0073] Step 3: The wood precursor loaded with ZIF-67 in step 2 is washed with deionized water for multiple times, and then placed in a refrigerator for 24 hours. The cold-treated sample is placed in a vacuum freeze dryer and vacuum freeze-dried at -50°C for 48 hours. The sample is then transferred to a tubular furnace and carbonized at 750°C in a nitrogen atmosphere to obtain a carbonized ZIF-67-loaded wood carbon material, i.e., ZIF-67@wood carbon material.
[0074] Step 4: Mix KBr, Bi(NO3)3 and deionized water in a 50mL polytetrafluoroethylene reactor to form a BiOBr precursor solution (solution C), place the carbonized ZIF-67@wood carbon material in 30mL of the BiOBr precursor solution for hydrothermal reaction, control the reaction temperature to 160°C, perform solid-liquid separation after the reaction, and finally, wash it with deionized water several times, move it to an oven and dry it at 60°C to obtain a bismuth oxyhalide carbon composite material.
[0075] Among them, the mass ratio of MOFs to wood carbon is 1:(10~100).
[0076] The solutes of the BiOBr precursor solution are KBr and Bi(NO3)3 (both 0.033 mol / L), and the solvent is deionized water.
[0077] Example 2
[0078] The preparation method of the bismuth oxyhalide carbon composite material provided in this embodiment is the same as that of Example 1 except that the concentration of KBr in Example 1 is replaced with 0.017 mol / L. The remaining process steps and process parameters are the same as those in Example 1.
[0079] Example 3
[0080] The preparation method of the bismuth oxyhalide carbon composite material provided in this embodiment is the same as that of Example 1 except that the concentration of Bi(NO3)3 in Example 1 is replaced by 0.017 mol / L. The remaining process steps and process parameters are the same as those in Example 1.
[0081] Example 4
[0082] The preparation method of the bismuth oxyhalide carbon composite material provided in this embodiment is the same as that in Example 1 except that the concentrations of KBr and Bi(NO3)3 in Example 1 are both replaced by 0.017 mol / L. The remaining process steps and process parameters are the same as those in Example 1.
[0083] Comparative Example 1
[0084] This comparative example provides a method for preparing a bismuth oxyhalide carbon composite material. Except that the carbonized ZIF-67@wood carbon material is replaced by a wood carbon material that is directly carbonized without ZIF-67 loading, the remaining steps and process parameters are the same as those in Example 1.
[0085] Comparative Example 2
[0086] This comparative example provides a method for preparing a bismuth oxyhalide carbon composite material. Except that the carbonized ZIF-67@wood carbon material is replaced by a wood carbon material that is directly carbonized without ZIF-67 loading, the remaining steps and process parameters are the same as those in Example 2.
[0087] Comparative Example 3
[0088] This comparative example provides a method for preparing a bismuth oxyhalide carbon composite material, except that the carbonized ZIF-67@wood carbon material is replaced by a wood carbon material that is directly carbonized without ZIF-67 loading, and the remaining steps and process parameters are the same as those in Example 3.
[0089] Comparative Example 4
[0090] This comparative example provides a method for preparing a bismuth oxyhalide carbon composite material, except that the carbonized ZIF-67@wood carbon material is replaced by a wood carbon material that is directly carbonized without ZIF-67 loading, and the remaining steps and process parameters are the same as those in Example 4.
[0091] In order to verify the technical effects of the embodiments and comparative examples, the following experiments were conducted.
[0092] Experimental Example 1
[0093] Observe the morphology of the raw materials at different processing stages in Example 1, as shown in FIG. Figure 1 As shown. Among them, Figure 1(a) is natural wood, (b) is the wood precursor loaded with ZIF-67, (c) is the carbonized ZIF-67@wood carbon material, and (d) is the bismuth oxyhalide carbon composite material. Figure 1 As shown, after the wood is loaded with ZIF-67, the color changes from yellowish to purple-red, accompanied by a small lateral shrinkage. After pyrolysis and carbonization in an inert atmosphere, the lateral size is reduced by 20%. After loading BiOBr nanosheets, the surface becomes slightly white.
[0094] At the same time, the morphology of the bismuth oxyhalide carbon composite material in Example 1 was detected. Figure 2 As shown in the figure, it can be seen that a large number of ZIF-67 polyhedral particles and BiOBr nanosheets are loaded on the inner surface of the pores of the bismuth oxyhalide carbon composite material, thereby providing more active sites for contact with the solution, accelerating the water evaporation rate and the degradation rate of organic pollutants.
[0095] Experimental Example 2
[0096] For the X-ray diffraction patterns in Example 1 and Comparative Examples 1 to 3, Figure 3 In the bismuth oxyhalide carbon composite material, multiple strong diffraction peaks of C, Co and BiOBr can be seen. The XRD spectrum of the prepared sample shows that the sample has high crystallinity and no impurity peaks, indicating that the series of samples were successfully prepared.
[0097] Experimental Example 3
[0098] The water evaporation performance of the bismuth oxyhalide carbon composite materials provided in Examples 1 to 4 and Comparative Examples 1 to 4 was tested, and the specific results are shown in Table 1.
[0099] The specific detection method is as follows: During the measurement of the photothermal water evaporation experiment, a 300W xenon lamp with a 420nm filter is used to simulate natural light, and an optical power meter is used to control the light intensity. The light intensity can be adjusted by changing the current in the range of 14 to 16A at a voltage of 14V and adjusting the distance between the solar simulator and the evaporator. The evaporation process is carried out in a beaker placed in an incubator to maintain a stable temperature environment. During each experiment, the beaker is filled with simulated seawater. The change in the mass of water is manually recorded every 10 minutes using an electronic balance to calculate the water evaporation rate. The surface temperature of the sample during the evaporation process is recorded with an infrared camera. The photothermal water evaporation experiment was carried out at room temperature ~21°C and ambient humidity ~50%. A 3.5wt% NaCl solution was used to simulate real seawater.
[0100] The overall steam generation efficiency (η) can be calculated using the following formula:
[0101] η=(mh LV ) / q
[0102] Where m is the evaporation rate of water under sunlight, q is the incident power density of sunlight during the steam generation experiment, and h is composed of sensible heat and vaporization enthalpy. LV Use the following formula to calculate:
[0103] h LV =CΔT+Δh
[0104] Where C is the specific heat of water, which is 4.18 J g -1 K -1 is a constant, ΔT is the temperature rise of water, and Δh is the enthalpy of vaporization relative to temperature.
[0105] A water evaporation device was used to purify 50ppm of methyl orange (MO) and methylene blue (MB) quasi-organic wastewater.
[0106] Table 1 Photothermal water evaporation performance
[0107]
[0108] It can be seen from the data in Table 1 that the photothermal water evaporation performance of the bismuth oxyhalide carbon composite material provided in Example 1 of the present invention is better than that of the comparative example as a whole.
[0109] Among them, taking Examples 1 to 4 and blank experiments as representatives, the water evaporation rate of the samples under 1 sun was tested. Figure 4 As shown in the figure, it can be seen that the photothermal evaporation performance of the bismuth oxyhalide carbon composite material prepared in Example 1 is significantly better than that of other examples. This may be because the ZIF-67 particles fill the pores on the inner surface of the wood channel, inhibit the shrinkage of the wood during carbonization, and accelerate the mass transfer process of water inside the wood. At the same time, the doping of the BiOBr flake structure also increases the effective evaporation area of the wood carbon material.
[0110] Experimental Example 4
[0111] The photocatalytic degradation performance of the bismuth oxyhalide carbon composite material provided in Example 1 and Comparative Example 1 for rhodamine b (RhB) was tested, and the specific method included: using a 300W xenon lamp equipped with a 420nm filter as a visible light source, and evaluating the photocatalytic activity of the prepared photocatalyst by degrading RhB dye. In short, in 100mL RhB solution (20mg L- 1) was added with 150 mg of photocatalyst, and the suspension was stirred in the dark for 30 min before irradiation to ensure adsorption-desorption equilibrium. Then, 6 mL of the suspension was collected every 5 min, centrifuged at 10,000 rpm for 5 min, and filtered through a 0.1 μm microporous filter to completely remove the catalyst powder. The supernatant was measured at an absorption wavelength of 554 nm using a UV-visible spectrophotometer to evaluate the concentration of RhB. The removal rate of RhB can be calculated as follows:
[0112] E t =(1-C t / C0)×100%
[0113] Among them, C0 and C t represent the initial concentration and residual concentration of RhB at time t, respectively.
[0114] like Figure 5 As shown, the photocatalytic degradation performance of RhB in Example 1 (97.60%) was significantly better than that in Comparative Example 1 (52.97%) and pure BiOBr (87.65%) when the degradation was performed for 20 min. This may be because the carbonized ZIF-67@wood carbon material has excellent adsorption performance for RhB, so that the RhB on the surface of the BiOBr nanosheets is fully adsorbed and oxidized, thereby greatly improving the photocatalytic degradation performance of the sample.
[0115] like Figure 6 As shown in the cyclic stability experiment, after 5 cycles, the degradation rate of RhB in Example 1 at 20 min was still as high as 87.87%, showing excellent stability.
[0116] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A bismuth oxyhalide carbon composite material, characterized in that: The invention comprises wood carbon and bismuth oxyhalide composited on the wood carbon.
2. The bismuth oxyhalide carbon composite material according to claim 1, characterized in that: The bismuth oxyhalide is any one of bismuth oxychloride, bismuth oxybromide or bismuth oxyiodide; The mass ratio of bismuth oxyhalide to wood carbon is 1:(50-200).
3. A method for preparing a bismuth oxyhalide carbon composite material, characterized in that: include Step 1: Mixing a transition metal salt and a solvent to prepare a solution A, placing wood in the solution A to load the transition metal on the wood by a hydrothermal method, and then performing solid-liquid separation to obtain a wood precursor loaded with the transition metal; Step 2: Mixing an organic ligand and a solvent to prepare a solution B, placing wood in the solution B, loading MOFs on the wood precursor by a hydrothermal method, and then performing solid-liquid separation and freeze drying to obtain a wood precursor loaded with MOFs; Step 3: Carbonizing the wood precursor loaded with MOFs in step 2 at high temperature under an inert atmosphere to obtain a MOFs-loaded wood-derived carbon material; Step 4: Mix the bismuth salt, the halide salt and the solvent to form a solution C, prepare bismuth oxyhalide on the MOFs-loaded derived wood carbon material by a hydrothermal method, and then separate the solid and liquid to obtain a bismuth oxyhalide carbon composite material.
4. The method for preparing a bismuth oxyhalide carbon composite material according to claim 3, characterized in that: In step 1: The transition metal salt is any one of nickel salt, iron salt, zinc salt or cobalt salt; The solvent is any one or more of methanol, anhydrous ethanol or deionized water.
5. The method for preparing a bismuth oxyhalide carbon composite material according to claim 4, characterized in that: In step 2: The organic ligand is any one of 2-methylimidazole, 4-methylimidazole, 4,5-methylimidazole and 4,4'-methylimidazole; The solvent is one or more of methanol, anhydrous ethanol and deionized water; The mass ratio of MOFs to wood precursor is 1:(10-100).
6. The method for preparing a bismuth oxyhalide carbon composite material according to claim 5, characterized in that: In steps 1 and 2: The concentrations of the transition metal salt in step 1 and the organic ligand in step 2 are both 0.1-1.0 mol / L; The hydrothermal temperature is 50-100°C and the time is 10-20h; The freeze-drying temperature is -20 to -50°C and the time is 24 to 48 hours.
7. The method for preparing a bismuth oxyhalide carbon composite material according to claim 6, characterized in that: In step 3: The carbonization temperature is 600-900°C and the carbonization time is 1-3h; The carbonization heating rate is 3-10°C / min; the flow rate of the inert gas flow is 50-200mL / min.
8. The method for preparing a bismuth oxyhalide carbon composite material according to claim 6, characterized in that: In step 4: The concentrations of bismuth salt and bromide salt are both 0.1-1.0 mol / L; The hydrothermal temperature is 100-200°C, and the hydrothermal time is 3-10 hours.
9. The method for preparing a bismuth oxyhalide carbon composite material according to claim 8, characterized in that: In step 4: The bismuth salt is any one of bismuth nitrate, bismuth chloride and bismuth sulfate; The halide salt is any one of potassium halide and sodium halide; The solvent is one or more of glacial acetic acid, anhydrous ethanol and deionized water.
10. The bismuth oxyhalide carbon composite material prepared by the method according to any one of claims 3 to 9, characterized in that: It is used for coupling solar energy water evaporation or photocatalytic degradation of oily wastewater.